Relationships between boring sponge assemblages and the availability of dead coral substrate on Mexican Pacific coral reefs. (26th October 2018) - Nava, Héctor; García-Madrigal, Carlos Alberto Emmanuel; Carballo, José Luis
Abstract: Boring sponges are an important component of bioeroder assemblages in tropical coral reefs. They are considered as a potential threat for coral reef health, and the increase of dead corals is expected to promote their abundance. The relationship between the availability of dead coral substrata and the development of boring sponge assemblages was evaluated during El Niño 2015–16 at five reefs from Zihuatanejo, Guerrero, Mexico. Environment and substrate quality were assessed. Overall, environment conditions remained normal in relation to previous studies in the area. Only water temperature showed unusually high records at all sites and coincided with bleaching and mortality of corals, possibly caused by the effects of the El Niño event. Abundance of boring sponges in dead corals and coral rubble was lower than during previous studies. Although sponge abundance was not directly related to cover of both dead corals and coral rubble, cover of dead corals showed a high correlation with the variation in the structure of sponge assemblages across sites. Cliona vermifera dominated sponge assemblages at all sites, and its abundance was high under conditions of high cover of live corals and low cover of bleached corals. Since overall sponge abundance responded in a similar way, these results suggest that boring sponge assemblages dominated by C. vermifera are enhanced by conditions favourable for corals. Our results imply that El Niño events in the Mexican Pacific are not likely to cause immediate population outbreaks of boring sponges.